Teh tarik ties: tackling elderly loneliness in Singapore - Chow, Nicole Hui Lin (Nanyang Technological University, 2024)
This paper presents Teh Tarik Ties, a communication campaign aimed at reducing loneliness among the elderly aged 60 and above living in Queenstown through community engagement and social activities. Over the course of our campaign, we organised four workshops and one final event, impacting over 100 seniors from Queenstown and forging multiple friendships. Additionally, we successfully raised awareness about the issue of elderly loneliness among our secondary audience aged 18-59 years old. Our campaign achieved its informational, attitudinal and behavioural objectives - a 25% increase in the number of respondents who had full knowledge of the community resources and facilities available, an increase in positive sentiments on the perceived quality of social interactions from a score of 3.47 to 4.18 and an increase in actions taken towards creating higher quality social interactions from a score of 3.45 to 4.29. A complete list of documents and research data can be found in the appendices.